Fabrication and Characterization of Epoxidized Natural Rubber Reinforced Single-Walled Carbon Nanotubes Nanocomposite - Asyadi Azam, Mohd; Mohamad, Noraiham; Mohd Warikh, Abd Rashid (2012)
The use of single-walled carbon nanotubes (SWCNTs) as a reinforcement in rubber nanocomposites nowadays attracts a great deal of attention. The rubber used in this study was epoxidized natural rubber (ENR) with SWCNTs as nanofiller. The influence of nanofillers on the mechanical and thermal properties of the produced nanocomposite was studied. SWCNT/ENR nanocomposite with 1 wt% of CNTs achieved maximum tensile strength at 13.64 MPa, which is 58 % higher than that of unmixed. With the addition of SWCNTs, the strength and elongation at break of the ENR decreased, and simultaneously, the strength modulus, tear resistance and hardness increased. Moreover, from the differential scanning calorimetry (DSC) analysis, the increase of Tm, Tc, and ΔHc were also confirmed.